PENGARUH PELATIHAN, LINGKUNGAN KERJA, DAN KEAHLIAN KOMUNIKASI TERHADAP KINERJA KARYAWAN (Studi Pada Perusahaan Daerah Air Minum Kota Cirebon) - Fadhil Aiman, 11.05.51.0092; Yunianto, Askar (Students Journal of Economic and Management, 2015)
This study takes an object on the regional water company Ciebon. The reason for the selection of object based researchwant to know the performance of the employee. From these gaps it is necessary to empandÂ research to analyze the effect of traning, wrk environment, and communication to employees perfomance. The research sample is purposive sampling method. Sample taken 100 people from a population of 268 people. Methods of data analyze using linear regression and methods of data collection using questionnaires. test results showed that (1) the training effect on the performance of employees showed a positive and significant effect (2) work environment affect the performance of the employees showed a positive and significant effect (3) communication skills affect the employees performance showed a positive and significant. Keywords : training, work environment, communication skills, and employee performance